Frequency of Wound Dehiscence in Posterior Sagittal Anorectoplasty in Children with Anorectal Malformations - Aabid, Saud; Rafi, Mazhar; Abdul, Reema; Rehman, Ammar Abdul; Khan, Rabia (Biological and Clinical Sciences Research Journal, 2025)
Wound dehiscence is a clinically important postoperative complication after sagittal anorectoplasty in children with anorectal malformations. Its occurrence may be influenced not only by surgical factors but also by demographic and socioeconomic conditions. Objective: To determine the prevalence of wound dehiscence after posterior sagittal anorectoplasty in children with anorectal malformations and to assess its association with demographic and socioeconomic variables. Methods: This descriptive cross-sectional study was conducted in the Department of Pediatric Surgery, Sheikh Zayed Hospital and Medical College, Rahim Yar Khan, from 23 May 2025 to 23 August 2025. A total of 129 children aged 1 month to 13 years undergoing posterior sagittal anorectoplasty were enrolled through consecutive sampling. Demographic and socioeconomic characteristics were recorded using a structured pro forma. Wound dehiscence was assessed clinically at the first postoperative follow-up visit on day 10. Data were analyzed using SPSS version 25. Quantitative variables were summarized as mean and standard deviation, while categorical variables were presented as frequencies and percentages. Post-stratification analysis was performed, and associations were tested using the chi-square test or Fisher’s exact test, as appropriate. A p-value of less than 0.05 was considered statistically significant. Results: Among 129 children, the mean age was 2.91 ± 1.77 years, and 61.2% were male. The overall prevalence of postoperative wound dehiscence was 30.2%. Wound dehiscence was significantly more frequent among children from rural areas than among those from urban areas (37.0% vs 18.8%; p=0.029). Higher proportions of wound dehiscence were also observed among children of illiterate mothers and those from low socioeconomic backgrounds, although these associations did not reach statistical significance. No significant association was found between wound dehiscence and age group or gender. Conclusion: Wound dehiscence occurred in nearly one-third of children after posterior sagittal anorectoplasty. Rural residence was significantly associated with a higher risk of wound dehiscence, suggesting that social and contextual determinants may influence postoperative outcomes in children with anorectal malformations.